PURIFICATION AND IMMOBILIZATION OF L-ASPARAGINASE ENZYME FROM THE THERMOPHILIC BACTERIA Bacillus licheniformis STRAIN HSA3-1a - AHYAR AHMAD; ABDUL MUIS PATTA; HASNAH NATSIR (International Journal of Pharma and Bio Sciences, 2013)
L-Asparaginase gives a great benefit in the cancer treatment, especially in acute lymphoblastic leukemia. L-Asparaginase is also proven to reduce the acrylamide content in the foods. The objective of this study was to perform immobilization and characterization L-Asparaginase produced from Bacillus licheniformis Strain HSA3-1a. The results showed that the free form L-Asparaginase from B. licheniformis HSA3-1a has optimum activity at pH 8 and 50oC, with a specific activity of 616.26 IU/mg protein and stabilized at the optimum pH and temperature for 60 minutes. The immobilized L-Asparaginase with activated glutaraldehyde-carbon carrier has optimum activity at pH 7 and 60°C with a specific activity of 499.27 IU/mg protein and stabilized at the optimum pH and temperature for 60 minutes. The immobilized L-Asparaginase can retain its activity by 84.79% after 2 times repeated use.